Monocaprin eye drop formulation to combat antibiotic resistant gonococcal blindness - Colin P. Churchward (Nature Portfolio, 2020)
Abstract Neisseria gonorrhoeae bacteria are acknowledged as an urgent threat to human health because this species has developed resistances to all of the antibiotics used clinically to treat its infections. N. gonorrhoeae causes the sexually transmitted disease gonorrhoea, but also causes blindness when the bacteria infect the eyes. Infants are particularly susceptible, acquiring the infection from their mothers at birth. We have shown that the monoglyceride monocaprin rapidly kills N. gonorrhoeae and other bacterial species and is non-irritating in ocular assays. Here we show that the physical and chemical properties of monocaprin make it ideal for use in a thickened eye drop formulation to combat eye infections. Monocaprin-containing formulations were assessed using analytical techniques and for antimicrobial activity in vitro and in ex vivo infections. Monocaprin-containing formulations retained activity after three years and are non-irritating, unlike preparations of povidone iodine in our assays. A recommended formulation for further development and investigation is 0.25% monocaprin in 1% HPMC with 1% polysorbate 20.